The usefulness of the Game Ready ™ vest for pre-cooling. - Dwyer, D.; Sanders, N.; Stefano, D.; Pruscino, C.; Withers, S. (National Elite Sports Council 2009 Athlete Services Forum - High Performance Programming for Success - 11-12th November - Satellite Program - Applied Physiology Conference 2009 - Australian Institute of Sport, Canberra - 10th, 11th and 13th November, 2009)
Pre-cooling the body before exercise by more than 0.3oC has been shown to offer performance benefits in certain types of sports1. A variety of techniques have been employed and evaluated in the past and present practices include the use of cooling vests or the application of ice towels and the ingestion of a slushie drink. The present pilot study examined the effectiveness of a relatively new type of cooling vest, which circulates cold water (4oC) through itself and uses pneumatic pressure to increase the surface area of cooling. Methods Three subjects completed three pre-cooling trials each in randomised order. Each trial began with the subject sitting in a heat chamber (34-38oC & 52-61%RH) for 15 minutes. Following this, one of three pre-cooling techniques was applied for 30 minutes, (TS) two towels drawn from an ice slurry and placed on the shoulders and thighs with a Gatorade slushie drink (14 ml/kg BW), (VS) the Game Ready (TM) vest with a Gatorade slushie drink (14 ml/kg BW) or (V) the Game Ready vest alone. Core temperature was measured every 5 minutes by an electronic capsule that transmits temperature to a handheld receiver. Results The application of the Game Ready vest alone caused a slight increase in core temperature of 0.16oC. The effect of the towels and slushie drink was a decrease in core temperature of 0.51oC after 30 minutes. The Game Ready vest and slushie drink also caused a decrease in core temperature of 0.59oC after 30 minutes. Core temperature continued to decline for both slushie drink techniques (TS & VS) for another 15 minutes after the end of the 30 min. pre-cooling treatment. TS caused a total decrease in core temperature of 0.68oC and VS 0.82oC. All three techniques were well tolerated by the subjects, although the towels were the least preferred option. Discussion/Conclusion These preliminary results indicate that the Game Ready vest may be at least as effective at decreasing core temperature as the application of ice towels, when both techniques are used in combination with a slushie drink. The data also indicate that the slushie drink per se may be responsible for most of the decrease in core temperature. The potential practical implications of these results are that the Game Ready vest is an effective pre-cooling technique when combined with a slushie drink that is more convenient than the use of towels and other vests that require refrigeration. Each Game Ready unit works with little preparation or supervision, can cool two individuals simultaneously and will work almost indefinitely without the need to recharge the vests in a freezer.